Rehabilitation with fixed prosthodontics associated with removable partial prosthesis: a 5-year follow-up clinical evaluation - Tassiana Cançado Melo Sá (2019)
Dental implants are a common and successful option for the rehabilitation of edentulous areas. However, there are some limitations to their use. The present clinical report describes a 5-year follow-up of maxillary rehabilitation using an attachment-retained removable partial denture (RPD) associated with fixed partial denture (FPD) units as an alternative to orthodontic treatment associated with orthognathic surgery and dental implant placement. Rehabilitation with fixed prosthodontics associated with a removable partial prosthesis was proposed. For greater precision and stability, a gold attachment was prepared. The patient was very satisfied with the rehabilitation and has been clinically followed for 5 years. In cases where the use of dental implants and/or conventional FPDs is limited or not indicate the association between an FPD and an RPD by means of attachments remains an important alternative to conventional clasp-retained RPDs